Frontonasal paramedian flap, a Marchac flap variation used for nasal tip reconstruction after basal cells carcinoma, a suitable option for large defects: case report - Ochoa Meza, Luis F.; Galvan Ruiz, Vanessa G.; Garay Hernandez, Carlos A.; Adolphs Orjuela, Hans F.; Dave, Rishita; McCall, Ileana P.; Toro Velandia, Adriana C.; Sanchez, Claudia K.; Zambrano, Karen D.; Ruiz-Velasco, Luis A. (International Surgery Journal, 2026)
Basal cell carcinoma (BCC) is the most common cutaneous malignancy encountered in clinical practice. Lesions frequently arise on sun-exposed facial areas, with the nose being particularly vulnerable. Oncologic management is often straightforward but reconstruction of functionally and aesthetically sensitive regions such as the nasal tip tends to be more complex. We present the case of a 64-year-old woman with a long-standing lesion involving the nasal tip without major symptoms; however, she noticed bleeding, pruritus, pain on palpation, and a mild ulceration. On examination, the lesion demonstrated clinical features suspicious for malignancy. A diagnostic biopsy was therefore performed and showed a nodular BCC infiltrating the superficial and reticular dermis, with the lesion in contact with the lateral surgical margin. Given these findings, surgical management was indicated. The patient underwent wide local excision of the lesion under appropriate anesthesia. Intraoperative margin evaluation confirmed complete tumor removal with histologically clear margins. The resulting defect of the nasal tip was reconstructed using a frontonasal flap, selected to provide reliable vascularity and adequate tissue match for this region. This case shows the importance of oncologic and reconstructive planning in the management of BCC of the nasal tip. It also supports the reliability of the frontal flap as a reconstructive option, providing acceptable functional and aesthetic results following tumor excision.